Brain responses to pitch changes in an acoustic environment in cats and rabbits - Ruusuvirta, Timo (1996)
Brain responses to pitch changes were measured in cats and rabbits. Event-related potentials (ERPs) were recorded from the hippocampus (cats and rabbits), cerebellar cortex, and visual cortex (rabbits). Additionally, multiple-unit activity (MUA) was measured in rabbits from the same trials and through the same electrodes as the ERPs. Pitch changes were introduced by presenting pitch deviant tones (deviants) in a sequence of homogenous repeated tones (standards). Differences in ERPs to the deviants and those to the standards (MMN-like ERPs) were found in recordings from the hippocampus and cerebellar cortex but not from the visual cortex. They did not occur before 75 ms from tone onset. MMN-like MUA was, in tum, present within the 20 ms latency in the hippocampus. The MMN-like responses reflected the different presentation rates of the deviants and standards only. Therefore, the responses did not resemble the mismatch negativity (MMN) observed in the cerebral cortex in humans and thought to represent a comparison process detecting a mismatch between a sensory input by the deviant and a short-term memory trace of the preceding standards. The hippocampal MUA recordings revealed a fast (latency less than 20 ms) increase in spike activity, particularly to the standards, suggesting that the higher stimulus presentation rate did not result in refractoriness on the part of those neural ensembles that were activated by the stimulation, as has been proposed in the case of the reduced amplitude of the Nl deflection of ERPs in humans. Three main conclusions can be drawn. First, instead of a separate comparison process, the different presentation rate of each type of stimulus per se is sufficient to explain the observed differences between responses to the deviants and those to the standards. Second, rather than neural refractoriness, this effect may represent an active process related to the formation of the short-term memory trace of repeated stimuli. Thirdly, since the effect of the stimulus repetition rate can be related to the memory trace, the trace seems to be widely distributed in the brain.